CFD simulation using wood (Cengal and Meranti) to improve cooling effect for Malaysia green building - Mazlan Mohamed; Mohd Hazim Mohamad Amini; Muhammad Azwadi Sulaiman; Mohamad Bashree Abu Bakar; Mohamad Najmi Masri; Nor Hakimin Abdullah; Nik Alnur Auli Nik Yusuf; Mohammad Khairul Azhar Abdul Razab; Zairi Ismael Rizman (2015)
In this study, heat transfer investigation is done in order to improve the cooling effect for green building without damaging the environment. This proposal is provoked by the desire to reduce the temperature for the green building and to sustain the environment and natural resources. The building industry is also a large consumer of non-renewable materials, and this trend has increased dramatically over the past century. To this end, we have been addressing sustainability concerns related to building construction materials through much research approach. It applied to building elements where we can collectively influence design, materials, construction, energy consumption and disposal. Comparison of temperature profiles of the material in the traditional wood house and green building model by using the constant temperature heat source and linearly varying temperature of the heat source for unsteady state is done. Also, the time for temperature to become steady is compared. The problem will be solved by using the software package FLUENTGAMBIT. The parameters under analysis focused on changing the influence of exterior walls in the energy consumption for cooling the building.